Clinical and histological features of head and neck melanoma: a population‐based study in France. (1st March 2015) - Dabouz, F.; Barbe, C.; Lesage, C.; Le Clainche, A.; Arnoult, G.; Hibon, E.; Bernard, P.; Grange, F.
Summary: Background: Head and neck melanomas (HNMs) account for an increasing proportion of melanomas and have a poor prognosis. Objectives: To compare the clinical and histological characteristics of HNMs with those of melanomas at other sites (MOS), and to identify pertinent clinicopathological subgroups of HNM. Methods: A retrospective population‐based study of incident in situ and invasive melanomas in the period 2004–2011 was performed. Results: HNMs represented 26·7% of 1548 melanomas, corresponding to a density ratio of 3·7 between HNMs and MOS. HNMs occurred later than MOS (71·2 vs. 58·4 years; P < 0·01), included a higher proportion of in situ cases (49·6% vs. 13·5%; P < 0·01) and were mainly lentigo malignant melanomas (73·0% vs. 2·6%; P < 0·01). Invasive HNMs included a higher proportion of thick (> 2 mm) tumours [33·7% vs. 24·1% ( P = 0·01); mean Breslow thickness: 2·18 vs. 1·77 mm ( P = 0·03)] and nodular melanomas (20·1% vs. 12%; P < 0·01). HNMs in the peripheral area of the head and neck differed from those of central location by a younger age of onset (65·2 vs. 72·4 years; P < 0·01), male predominance (64·4% vs. 33·8%; P < 0·01), and higher proportions of invasive (67·2% vs. 42%; P < 0·01) and nodular (15·1% vs. 7·5%; P = 0·01) melanomas. Conclusions: HNMs highly differ from MOS, and are clinically and histologically heterogeneous, possibly as a consequence of different patterns of sun exposure. These data could help to improve primary and secondary prevention messages for patients and doctors.